Viaje a la playa ebook - Jules, Jacqueline (Sofia Martinez., 2018)
Sofia and her family are headed to the beach for the weekend, and Sofia is packed and ready to go. But once they get to the beach house, it's obvious that Sofia did not pack basic beach gear. Will her beach trip be ruined?